(untitled) (Research, Society and Development, 2020)
Brazil is a country of great agricultural activity, resulting in high production of agro-industrial waste. In most cases, these residues not have industrial applications and can become a source of environmental pollution. This study aims to review the bioactive compounds present in tropical fruit residues and to verify their potential for use in the production of Fiber-Rich Powders (PRF). Qualitative bibliographic review was used as methodology. The compounds with effective beneficial health effects reviewed were phenolic compounds, carotenoids, vitamins (C, E and A) and alkaloids (trigonelline and caffeine). The data found for the PRF indicate good functional properties and high content of antioxidant compounds and dietary fibers. Thus, these materials to be used in the development of new products. In addition, we found that there are few studies about the bioaccessibility of powders produced from tropical fruit residues, which confirms the need for further studies on this topic. We emphasize that in addition to health benefits, the production of fiber-rich powders is an important alternative to reduce impacts on the environment due to the incorrect disposal of agro-industrial waste.